2017
DOI: 10.1073/pnas.1706247114
|View full text |Cite
|
Sign up to set email alerts
|

Trigger loop dynamics can explain stimulation of intrinsic termination by bacterial RNA polymerase without terminator hairpin contact

Abstract: In bacteria, intrinsic termination signals cause disassembly of the highly stable elongating transcription complex (EC) over windows of two to three nucleotides after kilobases of RNA synthesis. Intrinsic termination is caused by the formation of a nascent RNA hairpin adjacent to a weak RNA−DNA hybrid within RNA polymerase (RNAP). Although the contributions of RNA and DNA sequences to termination are largely understood, the roles of conformational changes in RNAP are less well described. The polymorphous trigg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 68 publications
2
24
0
Order By: Relevance
“…Second, we found that clamp movements are more important for dissociation of RNAP from DNA than for dissociation of RNA from the EC, which is the defining step in termination. Finally, we found that restricting movements of the TL markedly slowed the rates of both RNA and RNAP release, consistent with a role for TL-mediated conformational fluctuations in the termination process [14].…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…Second, we found that clamp movements are more important for dissociation of RNAP from DNA than for dissociation of RNA from the EC, which is the defining step in termination. Finally, we found that restricting movements of the TL markedly slowed the rates of both RNA and RNAP release, consistent with a role for TL-mediated conformational fluctuations in the termination process [14].…”
Section: Discussionsupporting
confidence: 73%
“…These effects on elongation, all of which caused corresponding changes in TE, are likely caused primarily by changes in pausing, which were evident in transcription elongation patterns ( Figure S1). Although we cannot exclude effects on on-pathway elongation, it is notable that the D-LF and C-LF disulfides that affect intrinsic termination only indirectly have large and opposite effects on a canonical hairpinstabilized pause [31], and that pausing is known to occur at intrinsic terminators [10,14].…”
Section: Clamp Conformation Has Stronger Effects On Elongation Than Omentioning
confidence: 99%
See 3 more Smart Citations